The Relation between the Critical Period for Accent Acquisition, National Identity (Jewish/Israeli) Assimilation, and Language skills - Shakkour, Wael; Lev, Yaniv; Abu, Salim Rabia (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
This study examines the correlation between Jewish/Israeli identity, pronunciation levels, the critical learning age period, and accent. The sample pool consisted of fifty Russian immigrant students and ten native-born Israeli citizens who were administered a 3-part questionnaire composed of questions relating to linguistic ability, heaviness of accent, and sense of Israeli identity. Accent was assessed by oral tests in which the participants were asked to perform various verbal tasks”such as repeating pseudo-words, pronouncing words with phonetic omissions, vocabulary tests, and listening-comprehension tests. Israeli identity was evaluated by a 23-item identity questionnaire. The findings indicate that a heavy accent is linked to a weaker sense of Israeli identity, the critical-age period also playing a central function in influencing vocabulary retention and learning skills. These parameters corresponded to the age of arrival in the country. No correlation was obtained between heaviness of accent and linguistic learning skills.